Virtual reality training system based on lower limb rehabilitation robot - Wang, Hongbo; Lin, Musong; Lin, Zhennan; Wang, Xincheng; Niu, Jianye; Yu, Hongfei; Zhang, Lili; Vladareanu, Luige (International Journal of Engineering and Technology, 2018)
This paper presents a virtual reality training system for the lower limb rehabilitation robot, which can simulate the bike riding and encourage patients to join in the recovery training through the built-in competitive game. The virtual reality training is a variable speed active training under the constraint trajectory, and it has adapting training posture function which can provide individual riding training track according to the legs length of patients. The movement synchronization between the robot and virtual model is achieved by interaction control strategy, and robot can change the training velocity based on the signal from feedback terrains in game. A serious game about bike match in forest was designed, and the user can select the training level as well as change perspective through the user interface. The training can be paused at any time, and the timer function could reflect the recovery of patient.Â